Penguatan Narasi Atraksi Wisata dan Kapasitas Pemandu Lokal di Kampung Wisata Sosromenduran, Yogyakarta - Yusuf, Mohamad; Raharjana, Destha Titi; Aji, Khusnul Bayu (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2025)
The community development activities conducted by the Center for Tourism Studies at Gadjah Mada University (UGM) in 2024 took place in Sosromenduran Tourism Village, located in Gedongtengen Subdistrict, Yogyakarta. This tourism village, situated in the heart of Yogyakarta near Malioboro, possesses diverse potential and attractions that can be further developed to enhance the overall visitor experience in Yogyakarta. The primary objective of this initiative is to improve the capacity of tourism managers, particularly in strengthening the narrative of tourism attractions, which is implemented through the development of storytelling techniques outlined in a guidebook. The approach employed in this program is known as Participatory Action Research (PAR), which involves a collaborative and action-oriented research. In practice, PAR is carried out through several methods, including tourism discussions/dialogues (sarasehan), field observations, and in-depth interviews. The outcomes of this community engagement effort include the development of narratives for seven neighborhoods (kampungs) within Sosromenduran Village. Each neighborhood is identified by its unique identity and complementary tourism products. Another significant output is the creation of a guidebook designed to serve as a reference for local guides in Sosromenduran Tourism Village to introduce its attractions to visitors. Additionally, this guidebook is supplemented with thematic maps illustrating the distribution of tourism attractions across the seven neighborhoods in Sosromenduran Tourism Village. === Kegiatan desa binaan yang dilaksanakan Pusat Studi Pariwisata UGM tahun 2024 dilaksanakan di kampung wisata Sosromenduran, Kemantren Gedongtengen, Yogyakarta. Kampung wisata yang terletak di pusat kota Yogyakarta yaitu Malioboro memiliki beragam potensi dan atraksi yang dapat ditingkatkan melengkapi pengalaman wisatawan selama di Yogyakarta. Secara umum, tujuan pendampingan untuk meningkatkan kapasitas pengelola wisata, khususnya dibidang penguatan narasi atraksi wisata yang dikemas dalam pengembangan storytelling yang diwujudkan dalam guidebook. Pendekatan yang dipergunakan adalah melalui Participatory Action Research (PAR) atau yang lebih dikenal dengan kaji tindak. Dalam praktiknya, PAR ini diwujudkan melalui beberapa metode, seperti diskusi/sarasehan pariwisata, pengamatan lapangan (observasi), dan indepth-interview. Hasilnya, pendampingan ini mampu menghasilkan narasi dari tujuh kampung yang melingkupi Kelurahan Sosromenduran. Masing-masing kampung memiliki identitas dan produk wisata yang saling melengkapi. Hasil lainnya berupa guidebook dapat dihasilkan untuk menjadi pegangan bagi pemandu lokal dari kampung wisata Sosromenduran untuk mengenalkan daya tariknya kepada wisatawan. Dan, dilengkapi dengan peta tematik sebaran daya tarik wisata di tujuh kampung yang berada di kamwis Sosromenduran.